Mental illness and injuries: emerging health challenges of urbanisation in South Asia. (11th April 2017) - Nambiar, Devaki; Razzak, Junaid; Afsana, Kaosar; Adams, Alayne M; Hasan, Arif; Mohan, Dinesh; Patel, Vikram
Abstract : Rapid unplanned urbanisation in South Asia has overlooked the health needs of poor and marginalised people. Devaki Nambiar and colleagues examine the problems of mental illness and injuries, and call for renewed political and financial commitment to urban health